Protective factors for early initiation of breastfeeding among Brazilian nursing mothers - Giovana Gaglianone Lemos; Taciana Maia de Sousa; Rafaela Cristina Vieira e Souza; Larissa Bueno Ferreira; Cristianny Miranda; Luana Caroline dos Santos (Frontiers Media S.A., 2023)
ObjectivesEvaluate the protective factors associated with early initiation of breastfeeding.MethodsCross-sectional study conducted with Brazilian nursing mothers. Breastfeeding in the first hour of life and difficulty initiating breastfeeding in the birth room were adopted as outcome variables and associated with other maternal and child information. Poisson regression was conducted to synthesize the data.ResultsAmong 104 nursing mothers evaluated, 56.7% reported breastfeeding in the first hour of life and 43% had difficulty initiating breastfeeding in the birth room. There was a higher prevalence of breastfeeding in the first hour of life among mothers with previous breastfeeding experience (PR = 1.47, 95% CI 1.04-2.07). Difficulty initiating breastfeeding in the birth room was more prevalent among mothers who did not receive breastfeeding guidance during antenatal care (PR = 2.83, 95% CI 1.43-4.32) and those without previous breastfeeding experience (PR = 2.49, 95% CI 1.24-6.45).ConclusionThese findings highlight the importance of adequate professional guidance, especially for primiparous mothers.